Jean-Baptiste Say : Revolutionary, Entrepreneur, Economist. - Schoorl, Evert (Routledge studies in the history of economics., 2012)
This volume is the first full-length biography of Jean-Baptiste Say (1767-1832), the most famous French classical economist. During his lifetime Say actively took part in three revolutions: the French Revolution, the Industrial Revolution and the establishment of economics as an academic discipline. He struggled with Bonaparte, was the owner of a cotton spinning mill, and published his famous Treatise of political economy and many other economic writings.